The impact of the Coronavirus pandemic on the performance of economic sectors globally, with refer to Iraq (Entrepreneurship Journal for Finance and Business, 2023)
The study aimed to identify the impact that the spread of the Corona Virus pandemic had on the global economy, and on the performance of the economic sectors in the world, with reference to the impact it had on the Iraqi economic sectors during the outbreak of the epidemic; In order to achieve the goal of the study, the descriptive analytical method was relied upon by presenting the performance of economic sectors globally and in Iraq; The study concluded that the Corona virus pandemic led to a severe recession in the global economy unprecedented since the Great Depression; The study also found that the Corona virus pandemic caused a significant decline in the performance of economic sectors in varying proportions from one sector to another due to the impact of the closure policies that governments followed in order to control the spread of the pandemic; The pandemic revealed the weakness of the health sector in the world in general, especially in Iraq, where the health sector has been neglected for many years; The study also found that the tourism sector was the most affected sector compared to other sectors that managed to recover gradually after easing the closure measures.